QTL associated with resistance to cassava brown streak and cassava mosaic diseases in a bi-parental cross of two Tanzanian farmer varieties, Namikonga and Albert - Masumba, E.A.; Kapinga, F.; Mkamilo, G.S.; Salum, K.; Kulembeka, H.P.; Rounsley, S.; Bredeson, J.V.; Lyons, J.B.; Rokhsar, D.S.; Kanju, E.; Katari, M.S.; Myburg, A.A.; et al. (Springer, 2017)
Cassava production in Africa is compromised by cassava brown streak disease (CBSD) and cassava mosaic disease (CMD). To reduce costs and increase the precision of resistance breeding, a QTL study was conducted to identify molecular markers linked to resistance against these diseases. A bi-parental F1 mapping population was developed from a cross between the Tanzanian farmer varieties, Namikonga and Albert. A one-step genetic linkage map comprising 943 SNP markers and 18 linkage groups spanning 1776.2 cM was generated. Phenotypic data from 240 F1 progeny were obtained from two disease hotspots in Tanzania, over two successive seasons, 2013 and 2014. Two consistent QTLs linked to resistance to CBSD-induced root necrosis were identified in Namikonga on chromosomes II (qCBSDRNFc2Nm) and XI (qCBSDRNc11Nm) and a putative QTL on chromosome XVIII (qCBSDRNc18Nm). qCBSDRNFc2Nm was identified at Naliendele in both seasons. The same QTL was also associated with CBSD foliar resistance. qCBSDRNc11Nm was identified at Chambezi in both seasons, and was characterized by three peaks, spanning a distance of 253 kb. Twenty-seven genes were identified within this region including two LRR proteins and a signal recognition particle. In addition, two highly significant CMD resistance QTL (qCMDc12.1A and qCMDc12.2A) were detected in Albert, on chromosome 12. Both qCMDc12.1A and qCMDc12.2A lay within the range of markers reported earlier, defining the CMD2 locus. This is the first time that two loci have been identified within the CMD2 QTL, and in germplasm of apparent East African origin. Additional QTLs with minor effects on CBSD and CMD resistance were also identified.